3D geological reconstruction of the M. Vettore seismogenic fault system (Central Apennines, Italy): Cross-cutting relationship with the M. Sibillini thrust. (February 2020) - Porreca, Massimiliano; Fabbrizzi, Andrea; Azzaro, Salvatore; Pucci, Stefano; Del Rio, Luca; Pierantoni, Pietro Paolo; Giorgetti, Claudia; Roberts, Gerald; Barchi, Massimiliano Rinaldo
Abstract: The 2016–2017 Amatrice-Norcia seismic sequence was triggered by the reactivation of a complex NNW-SSE trending, WSW-dipping normal fault system cross-cutting the Umbria-Marche fold and thrust belt near M. Vettore. This fault system produced clear and impressive co-seismic ruptures on normal faults in the hangingwall of the M. Sibillini thrust, whereas ruptures in the footwall were observed, but less clear. As a result, a strong controversy exists in the literature about the geometry of the seismogenic faults, their relationships with pre-existing thrusts, and the location of normal-faulting rupture tips. In this work, we present a 3D geological model of the M. Vettore area located between the Castelluccio basin and the outcrop of the M. Sibillini thrust, where the most evident co-seismic ruptures have been observed. The model shows the relationship between the ruptured normal faults and the M. Sibillini thrust, and was constructed using a grid of 14 geological cross-sections parallel and orthogonal to the main structural elements (i.e. normal faults and thrusts) down to a depth of 3 km. The model was built using reference structural surfaces, such as the top of the Early Cretaceous Maiolica Fm., the M. Sibillini thrust and the main seismogenic normal faults belonging to the M. Vettore fault system. The 3D model has allowed us to calculate the vertical cumulative throw distribution for the M. Vettore normal faults. The cumulative geological throw of ca. 1300 m across the normal faults in the proximity of the M. Sibillini thrust indicates that the seismogenic fault system continues into the footwall of the thrust, displacing it in the sub-surface. The results of this study provide important constraints on the cross-cutting relationships between active normal and pre-existing compressional structures in seismically active areas, contributing to a better definition of the faults segmentation, and the related seismic hazard. Graphical abstract: Image 1 Highlights: A novel 3D geological model of the M. Vettore area (Central Italy) was constructed using a grid of 14 geological sections. The geometrical reconstruction demonstrates that the M. Vettore normal fault cuts and displaces the M. Sibillini thrust. The maximum geological throw of the M. Vettore fault is ca. 1380 m where maximum 2016 coseismic displacement is recorded.